现代汉语总结类话语标记浅析 = Discourse Markers of Summary in Modern Chinese - Xiuling, Cao; Liu, Liu (Sinología hispánica. China Studies Review, 2015)
总结类话语标记是人类语言共有的元话语 成分之一。现代汉语总结类话语标记包括“总 之”、“一句话”、“概括起来讲”、“总的 来看”等众多成员，根据构成成分及其结构关 系特点可以归纳为以“话/言”和“说/讲/ 看”为核心成分的名词和动词两个系列。总结 类话语标记分布在前后语段之间，构建的语篇 模式为“a，X，b”，在“要点概括”的总体语 义功能之下表达概括、推论、补充、转折、让 步等多种下位语义关系。总结类话语标记的语 篇组织功能和人际互动功能是其概念表达功能 语法化的结果，在这一过程中从基本话语发展 为元话语。 A discourse marker of summary is a common meta-discourse element in human languages. Discourse markers of summary in modern Chinese contains zong zhi, yi ju hua, gai kuo qi lai jiang, zong de lai kan and others, which can be summarized as nouns and pronouns centered by hua/yan, shuo/jiang/kan in correspondence of their construction elements and features of construction relation. Discourse markers of summary distribute near the front and back syntagms, through which the discourse model is constructed as “a, X, b”. This construction implies summary, inference, complementarity, transference, concession, and other semantic relation of subcategorization. The discourse organizing function and inter-personal interactive function of discourse markers of summary is the grammaticalization of the function of these concepts and in this process, the discourse markers of summary develops from basic discourse to meta-discourse.